TINGKAT KECEMASAN PADA IBU HAMIL SELAMA PANDEMI COVID-19 DI BEBERAPA WILAYAH INDONESIA : LITERATURE REVIEW - Yurissetiowati Yurissetiowati (FORUM ILMIAH KESEHATAN, 2021)
The case of Covid-19 are increasing significantly around the world in every day. In Indonesia, people of confirmed cases of Covid-19 is 2,178,272 people with a total death of 58,491. Pregnant women and their baby are representation of high risk population at during an infectious disease pandemic. The restriction of health services to the almost of all routine services, including maternal and neonatal health services, can make psychological problems for pregnant women and then become anxiety. The purpose of this literature review is to examine the psychological health problems of pregnant women during the Covid-19 pandemic with the anxiety experienced by pregnant women. The method in writing this article is make a review of the literature contained in the database of health journals indexed on google schoolar and searches through the official website. Articles are selected with the criteria of free full text and open access. The results of the literature study through the database found 735 articles. Total articles selected according to the inclusion criteria were 5 articles. Pregnant women in several cities in Indonesia during the Covid-19 pandemic mostly the same experienced of anxiety. These psychological disorders can make a risk to the fetus and can be fetal development disorders, premature babies and low birth weight babies. The conclusion of this literature review pregnant women is the high risk group during the Covid-19 pandemic. Social support is needed by pregnant women to reduce anxiety during this Covid-19 pandemic. These Support can be provided by husbands and families as well as health workers in health services so that pregnant women can feel more calm during the pregnancy process.Keywords: pregnant; anxiety; Covid-19ABSTRAK Kasus Covid-19 di seluruh dunia mengalami peningkatakan secara signifikan setiap harinya. Di Indonesia kasus yang terkonfirmasi Covid-19 berjumlah 2.178.272 jiwa dengan total kematian 58.491. Ibu hamil dan janinnya mewakili populasi dengan risiko tinggi selama pandemi penyakit menular. Pembatasan pelayanan kesehatan hampir ke semua pelayanan rutin termasuk di dalamnya pelayanan kesehatan maternal dan neonatal dapat menimbulkan masalah psikologis bagi ibu hamil yang kemudian menjadi kecemasan. Tujuan dari literatur review ini adalah untuk menelaah masalah kesehatan psikologis ibu hamil selama pandemi Covid-19 berupa kecemasan yang dialami ibu hamil. Metode dalam penulisan artikel ini adalah tinjauan literatur yang terdapat dalam database jurnal kesehatan yang trindeks di google schoolar serta penelusuran melalui website resmi. Artikel dipilih dengan kriteria free full text dan open access. Hasil studi literatur melalui database ditemukan sebanyak 735 artikel. Jumlah artikel terpilih sesuai dengan kriteria inklusi terdapat 5 artikel. Wanita hamil di beberapa wilayah Indonesia selama pandemi Covid-19 berlangsung sebagian besar mengalami hal yang sama berupa kecemasan. Gangguan psikologis ini dapat beresiko bagi janin berupa gangguan perkembangan janin, bayi lahir prematur hingga BBLR. Kesimpulan dari literatur review ini adalah ibu hamil merupakan kelompok yang sangat beresiko selama pandemi Covid-19 ini berlangsung. Dukungan sosial sangat dubutuhkan oleh ibu hamil untuk mengurangi kecemasan di masa pandemi Covid-19 ini. Dukungan dapat diberikan oleh suami dan keluargaserta tenaga kesehatan di pelayanan kesehatan sehingga ibu hamil bisa lebih merasa tenang dalam menjalani proses kehamilannyaKata kunci: hamil; kecemasan; Covid-19